The therapist, the group and I: how therapeutic alliance moderates the effect of group cohesion on outcomes - Vicente, Sofia (2021)
Purpose This study aims to investigate whether the influence of group cohesion on the outcomes depended on the levels of the therapeutic alliance. Design/methodology/approach Sixteen individuals with a substance use disorder who were undergoing treatment in a therapeutic community responded to therapeutic alliance, group cohesion, craving and outcomes measures after every therapeutic small group session for a period of six weeks. Data analysis was performed using hierarchical linear modeling. Findings Results indicate that the effect of group cohesion is stronger when there is a high therapeutic alliance between resident and therapist. Originality/value Even on group interventions, to enhance group cohesion effects on outcomes, therapists must foster higher therapeutic alliance levels. The findings point out the importance of studying the effect of common factors on outcomes.